Kajian Penerapan Pasal 27A Undang-Undang Informasi dan Transaksi Elektronik Pada Grup Percakapan - Ronny, Ronny (LOCUS MEDIA PUBLISHING, 2025)
This study aims to examine the application of Article 27A of Law Number 1 of 2024 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions (called the ITE Law) in group conversation, one of the applications of Article 27A UU ITE is must meet public knowledge. The research method used is the normative legal method, namely library research based on secondary data, namely referring to legislation, several court decisions, and research results. The conclusion of the study is that access to information in conversation groups can meet public knowledge if there are two things, namely there is a large group of people; and most of the members of the conversation group did not know each other. The categorization of open and closed conversation groups does not determine the purpose of the information in the conversation group to be publicly known.